Magnetic Particle Induction and Its Importance in Biofilm Research - Anderson, Amy M.; Spears, Bryan M.; Lubarsky, Helen V.; Davidson, Irvine; Gerbersdorf, Sabine U.; Paterson, David M. (IntechOpen, 2011)
None